Gender differences in early literacy and mathematics achievement and self-regulatory behaviours in the first year of school: An Australian study - Walker, S; Walker, Sue; Berthelsen, Donna (My University, 2017)
This paper presents analyses of gender differences in classroom behaviours (e.g. attentiveness and task persistence) and early academic outcomes. Data is drawn from Growing Up in Australia: The Longitudinal Study of Australian children (LSAC). In these analyses, data from Wave 1 data collection (2004) and Wave 2 data collection (2006) for the Kindergarten Cohort are used. A sample of 2315 children who were in Year 1 of school at Wave 2 data collection are the focus for the analyses reported. The analyses draw on teacher ratings of children’s literacy and language competence and mathematical thinking in Year 1 of school; as well as ratings of children’s self-regulatory behaviour in the classroom and level of problem behaviours. Girls were rated by their teachers as having better literacy and language outcomes that were predicted by more positive classroom behaviours. Results are discussed with respect to the influence of children’s classroom behaviours on academic learning at the beginning of formal schooling.
Keywords: Children -- School age; Child Development -- Cognitive; Childhood and child development; Child Development; Children; School age; Cognitive; Childhood and child development